Recent Applications and Influences of Artificial Intelligence (AI) In Chemical and Allied Sciences - Anindya S. Manna; Antara Roy; Rajjakfur Rahaman; Prof Dilip Kumar Maiti (International Journal of Cheminformatics, 2024)
Artificial Intelligence (AI), the future tool of mankind that can revolutionise scientific research by making it faster, add more efficiently and accurately. During the pandemic situation, the scientific community was parted into two distinct groups, the computation-dependent community could easily continue their research work from their resident, while the works of the other group of researchers with lab-oriented research stopped entirely. In this connection use of AI becomes important and applied in various areas of chemistry and biochemistry for helping and enhancement of research towards the drug molecule development, retrosynthetic path finding of the targeted valuable compounds with their property prediction. Also, the possibility of applications of AI went beyond and applied in the food science and nano-technology through its experimental data dependent predictions for a faster and cost-effective research towards real applications. In this short review we discussed covering the different areas of chemistry and biochemistry, how AI is assisting the scientists in advancing these impactful research fields.
Keywords: AI in chemistry; Machine Learning; automated research tool; drug molecule design; synthetic route design